The effects of consuming a high protein diet (4.4 g/kg/d) on body composition in resistance-trained individuals - Peacock, A. J.; Ellerbroek, A.; Fromhoff, B.; Silver, T. (Journal of the International Society of Sports Nutrition, 2014)
Background: The consumption of dietary protein is important for resistance-trained individuals. It has been posited that intakes of 1.4 to 2.0 g/kg/day are needed for physically active individuals. Thus, the purpose of this investigation was to determine the effects of a very high protein diet (4.4 g/kg/d) on body composition in resistance-trained men and women.